PERANAN SEKOLAH SEBAGAI LEMBAGA PENGEMBANGAN PENDIDIKAN MULTIKULTURAL - Kholik, Nur (IAIIG Cilacap, 2017)
The purpose of this paper is to know the role of the school both in terms of the curriculum, teachers and also the material in the development of multicultural education, multicultural education as one of the solution to solve the conflict of the nation that is SARA.multikultural education should be instilled early to children so that children are able know how he interact other.With the environment and respect to othrer. therefore need the role of school in the development of multicultural is very needed education in order to aspire single ideals can be achieved. School as educational institutions should have developed multicultural education so that students can appreciate the differences that occur within the environment so that the harmony of society can be done.